Evaluation of Phytochemical Screening and Antibacterial Activity of Latana Camara Linn. Extract Used As Antibacterial Finish on Fabrics - M, Naseera S; R, Prabha (International Journal of Membrane Science and Technology, 2023)
The aim of the research was to evaluate the antibacterial activity of a crude extract from Latana camara L. on different types of fabric samples made of cotton, bamboo, and bamboo cotton. Lantana camara L. is a well-known weed and a popular ornamental garden plant that is widely utilized in traditional medicine all over the world. Acetate, ethanol, methanol, and petroleum ether were used as solvents to make the leaves crude extract. Escherichia coli and Staphylococcus aureus were used as test organisms for the crude extract’s anti-bacterial activity, which was also used for phytochemical analysis. According to a phytochemical study, Latana camara L. extract contained alkaloids, flavonoids, phenol and tannin. As measured by inhibitory zones ranging from 09mm to 24mm, plant methanol extract demonstrated good antibacterial activity against test organism. Antibacterial activity of fabrics (cotton, bamboo and bamboo cotton) finished with plant extract revealed inhibitory zones excellent ranging from 23mm to 28mm against Escherichia coli and Staphylococcus aureus. The present findings imply the potential antibacterial activity of the plant. L. camara aids in the relief of inflammatory conditions and to be developed into standardized, safe, and affordable biomedical products and use as functional finish for home textiles.